The method for calculating the bearing capacity of cold-formed C-Section axial compression member using Direct Strength Method (International Journal of Architecture and Urbanism, 2023)
The paper carried out numerical analysis using experimental and finite element analysis methods to determine the bearing capacity of cold-formed C-section axial compression member.Finite element analysis was performed using the application ABAQUS and the results were compared with experimental measurements.This paper also made out the reason for the error between the experimental results and the results of the finite element analysis, and the ultimate bearing capacity is determined by finite element analysis with C-section axial compression member of various sizes.At the same time, the effect of initial geometric imperfection on the bearing capacity of the member is analyzed in detail.Based on finding out that the supporting capacity of the member is directly related to local buckling, distortional buckling, and lateral-bending buckling critical stress, the formula for calculating the bearing capacity of the cold-formed C-section axial compression member by analyzing the research results on the direct strength method.